PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS TEKS PROSEDUR BERUPA VIDEO PADA MODEL SELF DIRECTED LEARNING - Sri Ismayah Aap; Deliani Deliani; Ali Ali (Jurnal Bahastra, 2022)
This study is a development research or often known as Research and Development (RD). It developed a learning media for writing procedure text in the form of video. The study used the research procedure proposed by Thiagarajan abbreviated as 4D (Define, Design, Development, and Dissemination) that was adapted and simplified into 3D, namely the Define, Design, and Development stages. The validation test was carried out by four experts; two media experts and two material experts. The research instrument used a validation sheet in the form of a questionnaire that used a Likert scale in the form of a checklist contained five kinds of answers in each question item given to material experts and media experts. The data obtained was quantitative that converted into qualitative data. The percentage data analysis was carried out to determine the percentage of product feasibility on learning media in the form of video. The percentage of the results of material and media validation shows that the media developed in this study is said to be feasible through several stages of assessment. As for the feasibility of the quality of the material from the development of this learning media, 84% of the first material experts with very valid qualifications and very decent categories, 69% of the second material experts with valid qualifications and proper categories, 81% of the first media experts with very valid qualifications and very feasible category and 100% of the second media expert with very valid qualifications and very feasible category. Based on the material and media aspect or overall learning media writing procedure text in the form of learning videos in this study is said to be very feasible use on Self Directed Learning Model.